Концептуальні підходи до організації розвитку інвестиційної діяльності підприємств на засадах парадигми економічної безпеки - Ємець, О. І.; Yemets, O. I. (Видавництво Львівської політехніки, 2017)
Розглянуто основні підходи до організації розвитку інвестиційної діяльності підприємств, що сприяє активізації інноваційної діяльності економічних агентів, дає змогу вирішувати соціально-економічні проблеми. Пропонується розробити концепцію управління розвитком інвестиційної діяльності підприємств, що ґрунтується на засадах парадигми економічної безпеки. Ця концепція виступатиме як теоретичне обґрунту- вання управління розвитку інвестиційної діяльності підприємств, відображатиме напрямки практичного її застосування, дасть змогу забезпечити міжгалузевий перелив капіталу, передбачити концепцію інноваційної трансформації науки і освіти та сформувати інноваційне середовище на засадах парадигми економічної безпеки.

The main approaches to the development of investment companies are considered, and they help to enhance innovation. It is proposed to develop the concept of development management investment companies, based on the principles of economic security paradigm. For each subject – economic security is a state of corporate resources (capital, personnel, information technology, laws) and entrepreneurial skills, which are guaranteed by the most effective use for their stable operation and dynamic scientific and technological and social development, prevention to negative internal and external threats. The main goal of economic security is to ensure its stable and maximally efficient operation today and a high potential for future development. In the article the existing theoretical approaches are considered to systematize the concept "development of investment enterprises" at different levels of economic science. The author singled out the following levels: international, macroeconomic, microeconomic, regional and industry. The investment activities of enterprises are often used at the microeconomic level, as common to the interpretation of an action, the transformation of investment resources (as a set of tools of different shapes) in investment product (business and other activities) for a purpose, appropriate development strategy. In view of the above, the main conceptual approach both in terms of the definition of "development of investment activity on the basis enterprises" and to manage them is a strategic approach; which is associated with the definition of goals and main areas of investment, creation of conditions for investment processes. The purpose of the article is to determine the priorities of investment companies, taking into account factors of economic security, to justify the need to increase investment attraction for sustainable economic development on the basis of management decisions. To achieve this goal it is necessary to perform the following tasks:to explore different approaches defining the essence of investment activity; to determine the content management aspect of investment on the basis of economic security paradigm. Significance of the study results are determined by the possibility of their use for decision-making in the management of economic security for development investment. The investment strategy is a structured set of several interrelated aspects, such as institutional, economic, legal, information-analytical. These aspects are interrelated, their structuring and allocation of priorities between them, in our opinion, allow you to have a clear idea of the development and implementation of investment strategy of the enterprise. Improving the current state of the economic situation in Ukraine is impossible without activating the investment of enterprises for sustainable development of priority sectors of the national economy and the threat of stagnation in Ukrainian industrial enterprises. Foreign direct investments should improve the international investment position of Ukraine and help to reduce external debt.
Conceptual approaches to development of investment activity on the basis enterprises paradigm of economic security
Keywords: інвестиційна діяльність; підприємство; економічна безпека; управління розвитком; investment; enterprise; economic security; development management; 330.322; 061.5; 65.012.8